Flow-through solvolysis enables production of native-like lignin from biomass. Issue 15 (12th July 2021) - Brandner, David G.; Kruger, Jacob S.; Thornburg, Nicholas E.; Facas, Gregory G.; Kenny, Jacob K.; Dreiling, Reagan J.; Morais, Ana Rita C.; Renders, Tom; Cleveland, Nicholas S.; Happs, Renee M.; Katahira, Rui; Vinzant, Todd B.; et al.
Abstract : Flow-through solvolysis offers an opportunity to limit lignin condensation reactions that prevent isolation of native lignin in biomass processing, thus allowing for the study of intrinsic lignin properties and steady-state lignin depolymerization. Abstract : The inherent reactivity of lignin in conventional biomass processing commonly prevents isolation of native lignin and limits monomer yields from catalytic depolymerization strategies that target aryl-ether bonds. Here we show that flow-through solvolysis with methanol at 225 °C produces native-like lignin from poplar, enabling the study of intrinsic lignin properties and evaluation of steady-state lignin depolymerization processes.